Design of Preventive Maintenance on the Electrical System of Agitator for Seed Precipitation Tank at PT Borneo Alumina Indonesia - Muhammaad Yusan Naim; Arif Jaya; Putra Rahmatullah (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
PT Borneo Alumina Indonesia is a company engaged in processing bauxite into alumina, where the reliability of the agitator system in the seed precipitation tank plays a crucial role in maintaining continuous production. However, failures in the agitator electrical system can lead to significant downtime, resulting in operational losses and decreased production efficiency. Therefore, this study aims to design an effective preventive maintenance schedule to improve system reliability and optimize production performance. The research applies Failure Mode and Effects Analysis (FMEA), Risk-Based Maintenance (RBM), and Reliability-Centered Maintenance (RCM), supported by Weibull distribution analysis to evaluate failure characteristics and determine optimal maintenance intervals. The results show that the proposed preventive maintenance strategy is effective in improving system reliability, with an increase of up to 13% compared to conditions without preventive maintenance. The maintenance plan includes routine inspections of critical components, as well as scheduled replacements at one-, two-, and three-year intervals integrated with annual overhauls. In addition, the implementation of this maintenance schedule reduces annual downtime to 3.84%, enabling alumina production to reach up to 96% of the theoretical capacity of 1,000,000 tons per year. In conclusion, the proposed maintenance strategy not only enhances equipment reliability but also supports sustainable operational efficiency in alumina production processes.